Dimensi Filsafat Komunikasi Hindu dan Moderasi Beragama dalam Ritual Melukat di Desa Suranadi - I Nengah Putra Kariana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study discusses the Melukat ritual practice in Suranadi Village, West Lombok, as a form of ritual communication that reflects Hindu spiritual values while also serving as a means of strengthening religious moderation in a multicultural society. Through a qualitative approach involving observation, interviews, and analysis within the framework of symbolic interactionism theory, this study found that ritual symbols such as tirtha (holy water), mantras, and bodily movements in Melukat are not only religiously meaningful but also form symbolic communication that connects humans, nature, and God. Hindu philosophical values such as tat tvam asi, ahimsa, and tri hita karana are manifested in the actions of the faithful, creating harmony within the self, society, and the cosmos. In the context of a diverse society, Melukat has proven to be an inclusive and tolerant practice. Its implementation is open to the participation of people of different faiths and is respected as part of the local cultural heritage. Thus, this ritual functions as an instrument for maintaining interfaith harmony. This study also emphasises the importance of symbolic interaction in the formation of shared meaning and collective identity. Recommendations are directed towards the development of comparative, interfaith, and interdisciplinary approaches to expand understanding of religious communication based on local traditions.